A study on time based for visual inspectors at Western Digital Batu Kawan production line - Puspavathi, S. Rama Naidu (2021)
This research is aimed to develop time-based guidelines that can help to preserve the optical health of the visual inspectors at SanDisk Storage Malaysia (a WD company). The research objectives is to identify the time patterns where defect escapees occur, to analyse relationship between time and visual acuity and also to develop time based guidelines for Visual Inspection operators. The method employed to analyse this is by analysing a set of data retrieved from the system called Defect Escapee data. This data is based on the number of drives inspected by first inspection station called VMI (Visual Manual Inspection)3 but then detected as reject in the second inspection station; FQA (Final Quality Assurance). Data analysis shows that there is a pattern between the time that had lapsed in continuous visual inspection task and the occurrences of escapee from VMI3 to FQA station. To confirm these findings two sets of controlled experiment was conducted on which the visual inspectors were given 15 minutes break after every 1 hour of inspection before they resume their visual inspection task. Another set, is where after every 1.5 hours of visual inspection task, the visual inspectors were asked to swap duties with mechanical assembly or manual related tasks before they return to their visual inspection tasks after 1.5 hours. In conclusion, there is a correlation between continuous inspection and defect detecting accuracy. The accuracy is inversely proportionate to time. The longer the time spent in continuous visual inspection, the lesser the visual inspection accuracy. This study is beneficial for organizations having visual inspection as part of their process. The research results able to give insight to the process owners to develop the most suitable work pattern for their employees stationed at Visual Inspection work cells. (Abstratct by author)